2017
DOI: 10.1007/s00277-017-3193-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-driver mutations in patients with JAK2V617F-mutated polycythemia vera or essential thrombocythemia with long-term molecular follow-up

Abstract: JAK2V617F monitoring and NGS of non-driver genes was performed in 100 patients with polycythemia vera (PV) or essential thrombocythemia (ET) with long molecular follow-up. Patients who did not progress to myelofibrosis (MF) or acute myeloid leukemia (AML) after more than 10 years (n = 50) showed a low frequency of mutations at first sample (18%) and an incidence rate of 1.7 new mutations × 100 person-years. Mutations were detected at first sample in 83% of PV/ET patients who later progressed to AML (n = 12) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 29 publications
5
30
0
Order By: Relevance
“…The prognostic relevance of TP53 , SF3B1 and U2AF1 mutations in ET and SRSF2 mutations in PV was previously recognized in our earlier study that also flagged EZH2 , LNK and IDH2 mutations in ET and ASXL1 and IDH2 mutations in PV in a similar capacity (Tefferi et al , ). The leukaemogenic potential of TP53 mutations(Lundberg et al , ; Rampal et al , ) and the prognostic potential of spliceosome gene mutations (Senin et al , ) in MPN has also been cited by others. Our findings regarding ET patients with spliceosome mutations having an increased risk of fibrotic transformation are consistent with the study by Grinfeld et al ().…”
Section: Discussionmentioning
confidence: 97%
“…The prognostic relevance of TP53 , SF3B1 and U2AF1 mutations in ET and SRSF2 mutations in PV was previously recognized in our earlier study that also flagged EZH2 , LNK and IDH2 mutations in ET and ASXL1 and IDH2 mutations in PV in a similar capacity (Tefferi et al , ). The leukaemogenic potential of TP53 mutations(Lundberg et al , ; Rampal et al , ) and the prognostic potential of spliceosome gene mutations (Senin et al , ) in MPN has also been cited by others. Our findings regarding ET patients with spliceosome mutations having an increased risk of fibrotic transformation are consistent with the study by Grinfeld et al ().…”
Section: Discussionmentioning
confidence: 97%
“…The clinical outcomes between patients with JAK2V617F mutations and those with JAK2 exon 12 mutations did not differ [18]. In JAK2V617F mutated PV patients, a persistently high or progressive increase in the JAK2V617F allele burden was the strongest predictor of MF transformation [19].…”
Section: Polycythemia Veramentioning
confidence: 86%
“…In particular, PMF patients with CALR¯/ASXL1 + mutational status have an inferior survival [192]. In NGS studies of patients with ET or PV, inferior OS or higher risk of leukemic transformation have been associated with mutations in ASXL1 [63,146,164], SRSF2 [146,164], IDH1/2 [164], or EZH2 (only ET) [186]. However, in a single gene study of 107 ET patients with ASXL1 mutations, they found no impact of ASXL1 on OS [194].…”
Section: High Molecular Risk Mutationsmentioning
confidence: 98%
“…However, median follow-up was only 10 years (range 1-13) and longer follow-up time may be needed to discover any difference. In addition, they found a higher probability of cytopenia during HU in patients carrying additional mutations in DNMT3A, SRSF2, IDH1/2 or RUNX1 compared to patients without [164]. Resistance to HU has been associated with leukemic transformation and shorter OS, particularly in patients developing cytopenia [226], highlighting the value of NGS in guiding therapy.…”
Section: Hydroxyureamentioning
confidence: 99%